Comparative analysis of adolescent intramedullary nailing and locking plate fixation for femoral shaft fractures - Jian Huang; Yiqun Bian (Frontiers in Surgery)
BackgroundFemoral shaft fractures in adolescents are commonly treated with either antegrade intramedullary nailing (AIN) or lateral plate (LP) fixation. This study compared the clinical outcomes of these two methods.MethodsAdolescent patients with femoral shaft fractures were randomly assigned to either the AIN group (n = 62) or the LP group (n = 62). Surgical parameters, early recovery metrics, levels of inflammatory cytokines, pain mediators, and bone metabolism markers were assessed.ResultsThe AIN group had significantly shorter incision lengths (6.8 vs. 8.5 cm, p < 0.001) and lower intraoperative blood loss (120 vs. 170 ml, p < 0.001) compared to the LP group. AIN patients began weight-bearing activities earlier (34 vs. 47 days, p < 0.01). Three months post-operation, the AIN group showed superior proximal femoral geometry and hip function, with a higher non-arthritic hip score (NAHS, 87 vs. 75, p < 0.001). One-week post-operation, the AIN group had lower serum levels of inflammatory cytokines and pain mediators, indicating a reduced inflammatory response and less postoperative pain.ConclusionsAIN offers significant advantages over LP in treating adolescent femoral shaft fractures, including reduced surgical trauma, faster early recovery, lower inflammatory response, less postoperative pain, and enhanced bone healing.